Exploring Teacher Creativity in Developing Project-Based Learning Models in Indonesian Elementary Schools - Raza, Amir; Akhtar, Shazia; Amin, Rafiullah (Journal of Loomingulisus ja Innovatsioon, 2024)
Teacher creativity plays a critical role in enhancing the quality of education, particularly in elementary schools. However, limited studies have explored how teachers develop innovative learning models tailored to students’ needs in the Indonesian context. This study aims to investigate the strategies employed by teachers to design project-based learning (PBL) models and assess their impact on students’ engagement and critical thinking skills. Employing a qualitative research method, data were collected through interviews, classroom observations, and document analysis involving 15 elementary school teachers across three regions in Indonesia. The findings reveal that teachers utilized diverse approaches, such as integrating local culture, leveraging digital tools, and fostering collaborative learning, to enrich PBL designs. Additionally, students exhibited increased motivation and improved problem-solving abilities when engaging in these models. However, challenges such as limited resources and training opportunities hindered optimal implementation. In conclusion, this study highlights the potential of teacher creativity in shaping effective PBL models and underscores the importance of institutional support for professional development. Future research should focus on scaling successful practices and addressing existing barriers.